PROCEDURES OF WELDING METAL PRODUCTS WITH MIG/MAG ROBOT WELDING - Krstevska, Aleksandra; Zdraveski, Filip; Bogatinoski, Zoran (Mechanical engineering scientific journal, 2023)
This research paper describes robot welding programming and different approach of three appli-cations in manufacturing processes by welding. It gives an overview of robot manipulator and its main components. For the experimental work a 6-axis robot arm is used and three different welds are made. Detailing of programming for every example with or without synchronization with the positioner and the trajectory is discussed. The paper presents steps of software development for online programming of a robot arm with or without synchronization.
Keywords: robot; welding; programming